2020
DOI: 10.3390/diagnostics10040246
|View full text |Cite
|
Sign up to set email alerts
|

Increased Tissue Expression of Lectin-Like Oxidized LDL Receptor-1 (LOX-1) Is Associated with Disease Severity in Chronic Rhinosinusitis with Nasal Polyps

Abstract: Background: The oxidative stress, induced by both environmental and intrinsic stimuli, underlies the onset and persistency of chronic rhinosinusitis (CRS). Scavenger receptors (SRs) are a broad family of transmembrane receptors involved in a dysfunctional host–environment interaction through a reaction with reactive oxygen species (ROS) production. Objective: We hypothesized possible roles of two major SRs in CRS pathology that can translate to clinical phenotypes or histological subtypes: lectin-like oxidized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Lipopolysaccharide reduces cystic fibrosis transmembrane conductance regulator (CFTR)-mediated short-circuit current and increases cytoplasmic and mitochondrial reactive oxygen species, resulting in CFTR carbonylation in mammalian respiratory epithelial cells [ 18 ]. Interestingly, lectin-like, oxidized low-density lipoprotein (LDL) receptor-1, a major receptor for oxidized LDL produced by oxidative stress, is associated with disease severity in CRSwNP [ 19 ], and bactericidal antibiotics promote oxidative damage and programmed cell death in sinonasal epithelial cells [ 20 ]. While some special genes have been targeted in research on CRS, a systemic analysis of the transcriptional levels in oxidative-stress-related genes in nasal polyposis remains lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Lipopolysaccharide reduces cystic fibrosis transmembrane conductance regulator (CFTR)-mediated short-circuit current and increases cytoplasmic and mitochondrial reactive oxygen species, resulting in CFTR carbonylation in mammalian respiratory epithelial cells [ 18 ]. Interestingly, lectin-like, oxidized low-density lipoprotein (LDL) receptor-1, a major receptor for oxidized LDL produced by oxidative stress, is associated with disease severity in CRSwNP [ 19 ], and bactericidal antibiotics promote oxidative damage and programmed cell death in sinonasal epithelial cells [ 20 ]. While some special genes have been targeted in research on CRS, a systemic analysis of the transcriptional levels in oxidative-stress-related genes in nasal polyposis remains lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that nasal epithelial cells, macrophages, neutrophils, eosinophils and basophils are the sites of oxidative stress in CRSwNP ( 13 , 14 , 16 ). In our study, NOS2 and NOX1 were expressed in epithelial and subcutaneous cells, such as NOS2 + macrophages, as determined by immunofluorescence.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there are many antioxidants in cells that can prevent the production of free radicals or eliminate them quickly, including glutathione (GSH), superoxide dismutase (SOD), catalase (CAT), heme oxygenase (HO) and glutathione reductase (GR) ( 10 ). Recently, oxidative stress has been shown to be involved in the development of CRSwNP ( 13 15 ). It was reported that patients with nasal polyps show an increase in oxidants and a decrease in antioxidants ( 16 – 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lectin-like oxidized LDL receptor-1 (LOX-1) is one member of these transmembrane receptors. In 2020, Nishida and colleagues found a significant increase in the mRNA expression levels of LOX-1 in CRSwNP patients [19].…”
Section: Chronic Rhinosinusitis (Crs) and Nasal Polyps (Np)mentioning
confidence: 99%